2021
DOI: 10.1016/j.jbc.2021.100534
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent conformational transitions of the insulin receptor–related receptor

Abstract: The insulin receptor (IR), insulin-like growth factor 1 receptor (IGF-1R), and insulin receptor-related receptor (IRR) form a mini family of predimerized receptor-like tyrosine kinases. IR and IGF-1R bind to their peptide agonists triggering metabolic and cell growth responses. In contrast, IRR, despite sharing with them a strong sequence homology, has no peptide-like agonist but can be activated by mildly alkaline media. The spatial structure and activation mechanisms of IRR have not been established yet. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…It was concluded that conformational rearrangements occur not only at the local level, as previously assumed [13], but also significantly change the overall shape of the ectodomain. The data obtained correspond to the conclusions of a recently published work, where a variety of forms of a full-size receptor similar to the insulin receptor was shown by atomic force microscopy [36].…”
Section: Model-independent Analysis Of the Minimum Number Of Components (Conformations) Of The Irr Protein In Solutionsupporting
confidence: 90%
“…It was concluded that conformational rearrangements occur not only at the local level, as previously assumed [13], but also significantly change the overall shape of the ectodomain. The data obtained correspond to the conclusions of a recently published work, where a variety of forms of a full-size receptor similar to the insulin receptor was shown by atomic force microscopy [36].…”
Section: Model-independent Analysis Of the Minimum Number Of Components (Conformations) Of The Irr Protein In Solutionsupporting
confidence: 90%
“…As noted above, the relatively hydrophilic surface regions ( Figure 2 A), which may serve as the potential specific patterns for TMD dimerization [ 39 , 40 ], can be identified in the TMD of each member of the insulin receptor subfamily. As revealed by recent structural studies of full-length receptors from this group [ 15 , 16 , 18 , 19 , 20 , 21 , 22 ], upon receptor activation, their TMD helices self-associate apparently via the N-terminal parts, as is typical for RTKs [ 39 , 40 , 43 , 44 ]. The N-terminal hydrophilic (polar) regions as potential dimerization motifs [ 39 , 40 ] adjacent to intramembrane prolines could be formed only in straight conformations of TMD helices, as demonstrated by us for IRRtm ( Figure 2 A,C) and previously proposed for IGF1R [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These states are characterized by small distances between the fibronectin domains and TMDs of the receptors. As it would be expected from the high sequence homology within the subfamily, IRR-ECD undergoes similar conformational transitions [ 22 ]. An additional “drop-like” shape of IRR-ECD with a short distance between the two membrane-proximal FnIII-3 domains was also described [ 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, little is known about the IRR, despite the close homology with the IGF1R and IR. No peptide or protein agonist have been so far identified but recent studies demonstrated that the IRR is an alkaline extracellular pH sensor with a role in the regulation of the acid-base balance [13,23,24].…”
Section: The Igf System: Major Components and Signal Transductionmentioning
confidence: 99%